Distance education in the school environment: integrating remote classrooms by video conferencing - Jukka Hussa (Journal of Open, Flexible and Distance Learning, 2012)
The instructional process in classroom focused distance education consists of features of conventional educational as well as elements from distance education. The theoretical and practical approach adopted in this article seeks to find the common features from both approaches and link them together. A theoretical framework for classroom focused distance education tries to capture some key features of the instructional process both on distance and on conventional education and to describe them in relation to each other. The article focuses on the issues how two separate classrooms that are connected to one instructional process can be handled simultaneously by one teacher.